Oblicz:
a) 4 4/9 x ( - 3 3/8 ) =
b) ( - 8 2/3 ) : ( - 1 4/9 ) =
c) 0,42: 0,3 x 0,5 / 2 2/9 - 1 2/3 =


Odpowiedź :

Odpowiedź:

a)

4 i 4/9 * ( - 3 i 3/8 ) =

= 40/9 * (- 27/8)=

= 5/1 * (-3/1)=

= - 15/1=

= - 15

b)

( - 8 i 2/3 ) : ( - 1 i 4/9 ) =

= - 26/3: ( - 13/9) =

= - 26/3 * (-9/13) =

= - 2/1 * (-3/1) =

= 6/1=

= 6

c)

0,42: 0,3 * 0,5

-------------------------  =

2  i 2/9 - 1 i 2/3

""" 1,4 * 0,5

= -------------------------- =

"""2 i 2/9 - 1 i 4/9

"""" 0,7

= ------------------------ =

"""20/9 - 13/9

"""" 0,7

= ------------- =

""  7/9

= 0,7 : 7/9 =

= 7/10 * 9/7 =

= 1/10 * 9/1=

= 9/10 =

= 0.9

Szczegółowe wyjaśnienie: